Dynamic Performance of Foam Concrete With Recycled Coir Fiber - Zhang, Junping; Li, Jing; Zhang, Liwen; Liu, Zhouqiang; Jiang, Zuqian (Frontiers in Materials, 2020)
Foam concrete, a new kind of building material, has attracted wide attentions due to its high energy absorption capability and low density. However, the low strength and poor toughness of foam concrete have become obstacles to hinder its further application. Coir fiber (CF), as a renewable recycled plant fiber, has shown a significant effectiveness on improving the mechanical properties of cement-based materials in some previous studies. In this paper, CF was introduced into foam concrete to develop its dynamic performance. A total of 54 foam concrete specimens with different CF contents (0.0%, 0.5%, 1.0%, 1.5%, 2.0%, and 2.5%) were prepared and divided into 6 groups. A single-impact test was carried out at three driving gas pressures (0.20MPa, 0.25MPa, and 0.30MPa) by means of Split Hopkinson pressure bar (SHPB) experimental technology to investigate the effect of CF content on the dynamic performance of foam concrete, including the failure mode, dynamic compressive strength, stress-strain behavior, and energy absorption capacity. Furthermore, to explain the change mechanism of CF-foam concrete, a microstructure analysis was conducted through scanning electron microscope (SEM) and X-ray diffraction (XRD). The results revealed that appropriate amount of CF could significantly improve the dynamic performance of foam concrete. The foam concrete’ ductility attained an optimal level at the CF content of 1.5%. The dynamic compressive strengths reached their highest values of 2.27MPa (at 0.20MPa gas pressure), 3.18MPa (at 0.25MPa gas pressure), and 4.21MPa (at 0.30 MPa gas pressure) at the CF content of 1.5%. The peak values of energy absorption were 8.9 J (at 0.20MPa gas pressure) at a CF content of 2.0%, 14.9J (at 0.25MPa gas pressure) at a CF content of 1.5%, and 22.4J (at 0.30MPa gas pressure) at a CF content of 1.5%, respectively. However, this improvement would deteriorate when CF was excess.